2021
DOI: 10.33774/coe-2021-119px
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in dietary behaviours and lifestyle as risk factors for weight gain during the covid-19 lockdown in chile: A cross-sectional study

Abstract: Domiciliary confinement of people is one of the main strategies to limit the impact of COVID-19. However, lockdowns have led to changes in lifestyle, emotional health, and eating habits. We aimed to evaluate the effect of changes in dietary behaviours and lifestyle on weight gain during the COVID-19 lockdown in Chile. In this crosssectional analytical study, five surveys were condensed into a single 86-item online questionnaire comprising general and sociodemographic history, eating habits before and during co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The authors also found longer quarantines to be associated with a greater desire for pleasant foods. On the other hand, an increase in fruit and vegetable cooking was associated with weight loss (Navarro-Cruz et al, 2021), whereas weight gain was associated with lifestyle deterioration during confinement and not due to emotional influence. As said before, women cooked more during the pandemic, and this could be related to significantly higher healthy eating index scores in female compared to male workers (Schifferli-Castro et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The authors also found longer quarantines to be associated with a greater desire for pleasant foods. On the other hand, an increase in fruit and vegetable cooking was associated with weight loss (Navarro-Cruz et al, 2021), whereas weight gain was associated with lifestyle deterioration during confinement and not due to emotional influence. As said before, women cooked more during the pandemic, and this could be related to significantly higher healthy eating index scores in female compared to male workers (Schifferli-Castro et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…The COVID-19 pandemic has had important impacts on living and eating habits worldwide. Weight gains of 10% modify the brain, causing personality impairments leading to impulsiveness and lesser resistance to desires (Navarro-Cruz et al, 2021). Due to at least temporary lockdowns and teleworking, for many people eating has shifted from at work canteens and restaurants to home cooking or food delivery (Ferrante et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation